THE FIRST STEP IN BUILDING ENTREPRENEURSHIP AMONG STUDENTS - Risha Febriyanti; Yulastri, Asmar; Yuliana (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The development of an entrepreneurial spirit among students has become an important priority for many schools and education stakeholders. This research aims to identify the early stages that are important in developing an entrepreneurial culture in the student community. The analysis method used is a qualitative approach involving observation, documentation studies, and fieldwork. The results of the study reveal three key elements that should be the focus for schools. First and foremost, schools must develop a curriculum that pays special attention to the development of students' knowledge and business acumen. In addition, educational institutions must provide extracurricular activities that enhance students' practical experience in running a business, such as running clubs and business projects. Third, developing relationships with local communities, including the business world, organizations, and local government agencies, can provide benefits for students in the form of practical practice and day-to-day support for business programs. The findings of this study emphasize the need for a holistic approach in building an entrepreneurial culture among students, which involves synchronizing integration, extracurricular programs, and external stakeholder engagement. These initial steps can be a strong foundation for schools to develop students into innovative and future-oriented entrepreneurs.